Export Competitiveness of Textile Commodities: A Panel Data Approach - Tarun Arora (FIW - Research Centre International Economics, 2015)
The Paper assesses the export competitiveness of top fifteen textile products (different for each export destination) at 6 digit level of HS classification exported by India to top seven textile export destinations by using both price and income export elasticities. The export elasticities are estimated using dynamic panel data approach for each country separately. Commodity specific elasticities are further estimated to forecast the exports of commodities exported to respective export destinations. The resulting estimates can be used in designing destination specific export promotion policies for India.
Keywords: F1; F14; F17; 330; Trade elasticities; Competitiveness; Forecasting